EFEKTIVITAS APLIKASI E-DUKCAPIL DALAM MELAKUKAN PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DESA TEGALWARU KECAMATAN CILAMAYA WETAN KABUPATEN KARAWANG - Syadiyah, Halimatus; Priyanti, Evi; Febriantin, Kariena (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2025)
The E-Dukcapil Karawang application is designed to make it easier for the public to access population administration services quickly, transparently and free of fraudulent charges (extortion). However, its implementation in Tegalwaru Village still faces various challenges. This research aims to measure the effectiveness of the application in providing optimal public services and identify the obstacles faced in community use. Using qualitative methods with a phenomenological approach, this research collects data through interviews, observation and documentation. The research results show that low digital literacy and minimal socialization are the main obstacles, which ultimately open up opportunities for extortion. Apart from that, it is considered that village officials do not fully understand the operation of the E-Dukcapil application, so they are unable to provide adequate assistance to the community. Therefore, it is necessary to increase outreach, intensify training for village officials, and provide technical assistance services to ensure that this application can be utilized optimally.